From Control Requirements to PIL Test: Development of a Structure to Autopilot Implementation - Marcelo H. Santos (IEEE, 2021)
This article presents the development of Autopilot (AP) blocks for a fixed-wing aircraft and the implementation of a Processor In the Loop (PIL) test platform. The AP entails the control, guidance, and navigation blocks. The control block design employed classical control theory considering a Piper 4 aircraft model, and the MILF-8785C design requirements standard. The PIL test platform is composed of an AP running in a microcontroller and a simulated aircraft on a PC (Personal Computer). The results of three missions carried out on the PIL platform are presented. In these missions, the performed maneuvers are such that lateral and longitudinal controls are required. In all three cases, all predefined waypoints are achieved, indicating the success of the developed AP project. The AP test implemented in a microcontroller that can be embedded onto an aircraft for a real flight mission indicates the usefulness of the developed PIL platform.